Ảnh hưởng của Luật kế toán 2015 đến độ tin cậy dồn tích của báo cáo tài chính: Bằng chứng thực nghiệm tại các công ty thuộc nhóm ngành công nghiệp - Hoàng Cẩm , Trang; Bùi Thị Ngọc, Hân; Trần Ân, Nguyên (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
The 2015 Accounting Law, which replaced the 2003 Accounting Law, marked a significant milestone in Vietnam’s accounting reforms, aiming for greater transparency and improved financial reporting quality in line with international standards. The study analyzes the impact of this legislative amendment on the reliability of accruals in the financial statements of listed industrial companies, using data from 784 observations before and after the law’s implementation. Findings reveal a significant improvement in accrual reliability, particularly in financial asset accruals, followed by long-term operational assets and working capital. This study provides valuable empirical evidence for policymakers. Additionally, it offers recommendations to strengthen regulatory oversight and enforcement, contributing to higher-quality accounting information, greater investor confidence, and the sustainable development of Vietnam’s industrial sector.